ANALYSIS OF THE RECRUITMENT AND SELECTION PROCESS OF HUMAN RESOURCES (HR) AT PERMATA PAMULANG HOSPITAL - Putri Amartya Alfiz; RR Arum Ariasih; Fini Fajrini; Noor Latifah (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
The need for Human resources is needed to fill the positions needed by a health service facility for the scope of employees, medical personnel, leaders, and other workers. In getting qualified employees, the hospital will select applicants when the recruitment is complete. Selection itself is an activity of separating applicants into two parts between being accepted and not being accepted. This research aims to look at the description of the selection or recruitment process for human resources (HR) at Permata Pamulang Hospital in 2022. This research uses a qualitative approach with a descriptive method. This research was conducted using in-depth interviews with informants about the views, beliefs, experiences, and knowledge of the informants' behavior regarding a matter as a whole. 3 informants in this study were key informants, main informants, and supporting informants. This research was conducted at Permata Pamulang Hospital from October 2022 to February 2023. The results of this study stated that recruitment planning would begin when a unit requested additional employees due to workload. After planning, Permata Pamulang Hospital will begin recruiting and selecting the desired human resources. Permata Pamulang Hospital conducts a selection of applications made by high-ranking officials such as HR, coordinators, and users from units that require new employees.